Naevi congenitales pigmentosi gigantei cutis - Stojanović, S... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1999)
Authors present the case of a 21-year-old female patient with the characteristics of the congenital pigmented hairy nevi. There were numerous changes in the form of the giant nevi, characterized by the pigmented, hairy appearance. All observed changes were present from birth and had dermatomical distribution on the skin of the trunk, upper and lower extremities and the face. According to the Wallace's rule of nine, total skin surface covered by the changes was about 20%. The patient did not observe changes in the color, size or distribution of the nevi during her life. Coexisting changes in the brain structures, which may indicate neurocutaneous melanosis, induced us to perform EEG and MRI examinations but the obtained results were negative. The extensive skin changes and the lack of evidence of malignant alteration of thenevi were the reasons we suggested further clinical surveillance and observation of the patient.
Keywords: Adult; Congenital; Diagnosis; Nevus, pigmented; Skin neoplasms